Classification of transformed anchovy products based on the use of element patterns and decision trees to assess traceability and country of origin labelling - Varrà, Maria Olga; Husáková, Lenka; Patočka, Jan; Ghidini, Sergio; Zanardi, Emanuela (Food chemistry, 2021)
Quadrupole inductively coupled plasma mass spectrometry (Q-ICP-MS) and direct mercury analysis were used to determine the elemental composition of 180 transformed (salt-ripened) anchovies from three different fishing areas before and after packaging. To this purpose, four decision trees-based algorithms, corresponding to C5.0, classification and regression trees (CART), chi-squareautomatic interaction detection (CHAID), and quick unbiased efficient statistical tree (QUEST) were applied to the elemental datasets to find the most accurate data mining procedure to achieve the ultimate goal of fish origin prediction. Classification rules generated by the trained CHAID model optimally identified unlabelled testing bulk anchovies (93.9% F-score) by using just 6 out of 52 elements (As, K, P, Cd, Li, and Sr). The finished packaged product was better modelled by the QUEST algorithm which recognised the origin of anchovies with F-score of 97.7%, considering the information carried out by 5 elements (B, As, K. Cd, and Pd). Results obtained suggested that the traceability system in the fishery sector may be supported by simplified machine learning techniques applied to a limited but effective number of inorganic predictors of origin.
Keywords: Mercury; algoritmy; Decision trees; Fish Products; Geographical origin; rozhodovací stromy; rybí výrobky; Animals; Fishes; Engraulis encrasicolus; Fish products; ICP-MS; Algorithms; Decision Trees; zvířata; rtuť; ryby; Data mining